The Activities of the Central Bank in a Pandemic - Pasichnik Irina V. (Bìznes Inform, 2020)
The article is aimed at identifying features in the implementation of monetary policy in the face of increasing crisis phenomena in the world economy caused by the pandemic. The activities and changes introduced by the central banks of the European Union, the USA, the United Kingdom to regulate the financial sector are analyzed. The activities of the National Bank of Ukraine for the beginning of 2020 to support the economy are researched, the main measures of support and forecasts of monetary policy for the current and next year are determined. The main instrument of monetary policy of the NBU is the discount rate (refinancing rate). By changing its value, the NBU affects the value of money resources – reduces to provide access or increases to restrict access to funds. At the beginning of 2020, the NBU reduced the interest rate to 8% – in order to help the business survive the time of quarantine. The main measures of central banks to support the banking system, financial stability and stimulate business activity are defined. Such measures may include the following: providing additional liquidity to banks through the monetary policy instruments; imposing restrictions on the operations and activities of commercial banks, etc. Refinancing rates by the G7 central banks have been co-ordinated and are currently around 0,25%. The priority paths of developments and the actions by central banks to restore the world economy are provided. Central banks soften monetary policy and provide liquidity to the economy in order to maintain the credit activity of banking institutions and provide the economy with the necessary resources. Thanks to these efforts, foreign countries, as well as Ukraine, will be able to restore economic growth and reach the pre-projected economic indicators.